Phenomenology Study on Career Travel and Decisions for Company Leaving Generation Y Employees in the Banking Sector - Octaviyanti Retno Palupi; Mirwan Surya Perdhana (Budapest International Research and Critics University, 2022)
This study aims to understand the antecedents of Generation Y employees in making decisions to leave companies in the banking sector. Researchers took 2 participants from 8 employees who left ABC bank from 2017 to 2019. Researchers used a qualitative phenomenological approach that can describe and describe phenomena without manipulating data so that data is available as it is. The method of collecting data is by means of semi-structured interviews where the process starts from the issues covered in the interview guide. In exploring research questions, 5 main themes were taken, including: 1). Pay for performance; 2). Career development; 3). Roles and leadership styles, 4). Company Policy (change of target) and 5). Work Life Balance. The results of this study stated that the main theme was not significant in the decision making of female employees to leave the company with the background of a family life journey. However, these five themes become one of the considerations for leaving the company when it is accompanied by employee dissatisfaction arising from other factors.